Photoconductive antenna and manufacturing method thereof
By using silicon nitride film and organic potting silicone packaging on terahertz photoconductive antennas, the problem of low emission power of terahertz photoconductive antennas is solved, and the device's voltage resistance and emission efficiency are significantly improved.
Patent Information
- Application Number
- CN202411790822.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
The transmission power of existing terahertz photoconductive antennas is low, resulting in limited efficiency in applications.
The packaging method of silicon nitride film and organic potted silicone is adopted to enhance laser absorption through the interference effect of silicon nitride film, and the insulation and thermal conductivity are increased by organic potting silicone, thereby improving the pressure resistance and emission efficiency of the device.
The voltage withstandability and radiation field strength of the terahertz photoconductive antenna is significantly improved, the terahertz wave amplitude is increased by about 6 times, and the terahertz spectrum width extends from 1.5 THz to about 3 THz.
Smart Images

Figure CN119812740A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of terahertz photoconductive antennas, and in particular relates to a photoconductive antenna capable of enhancing the pressure resistance, heat dissipation and light focusing of a device, thereby enhancing the terahertz emission intensity, and a manufacturing method thereof. Background Art
[0002] Terahertz waves refer to electromagnetic waves with a frequency range of 0.1 to 10 THz, which is located between the microwave band and the infrared band. Since the research on this band is not yet mature, it is also called the "terahertz gap". The terahertz band has both the high speed and large bandwidth of the infrared band and the unlimited transmission characteristics of the microwave band, so it is a key development technology for the next generation of communications. At the same time, terahertz waves have the characteristics of low energy and good penetration, and have great prospects in biological imaging, security detection, national defense, etc.
[0003] As a terahertz source, terahertz photoconductive antenna can emit wide-spectrum terahertz pulses. As an important component of terahertz time-domain spectrometer, it has a wide range of applications in spectroscopy research, drug testing, and non-destructive testing. Terahertz photoconductive antenna generates freely moving carriers through femtosecond laser irradiation, which accelerate and recombine under bias voltage and generate transient current, and then radiate terahertz pulses into space. This device has the characteristics of easy preparation, room temperature operation, and low cost. At present, the main problem facing terahertz photoconductive antenna is its low transmission power.
[0004] One of the most direct ways to increase the terahertz emission power is to increase the bias voltage of the device. Although the breakdown electric field strength of semi-insulating gallium arsenide is theoretically as high as 250kV / cm, the breakdown electric field strength of the actual device is much lower than the theoretical value due to thermal failure, tip discharge, surface flashover, etc. Therefore, a simple and stable packaging method is needed to improve the performance of the device.
[0005] Carl Headley et al. used (NH2)2S to encapsulate PCA. Shang-HuaYang et al. used SiO2 to encapsulate three-dimensional nanoelectrode PCA. Abhishek Gupta et al. used TiO2 with better insulation to encapsulate bowtie PCA. DVLavrukhin et al. used silicon nitride and aluminum oxide to passivate and encapsulate nanoelectrode PCA. There are many different methods for encapsulating photoconductive antennas, but how to improve the performance of the device through a relatively simple and stable process is an urgent problem to be solved. Summary of the invention
[0006] In order to increase the terahertz emission intensity of a terahertz photoconductive antenna, one of the objectives of the present invention is to provide a photoconductive antenna having silicon nitride and organic potting silica gel.
[0007] The technical solution adopted by the present invention to solve its technical problem is: a photoconductive antenna, including a semi-insulating gallium arsenide substrate and antenna electrodes centrally symmetrically distributed on the semi-insulating gallium arsenide substrate, the semi-insulating gallium arsenide substrate and the antenna electrodes are covered with a silicon nitride film, a circular opening for leading out the antenna electrode is opened on the silicon nitride film, the circular opening is smeared with conductive silver paste, the conductive silver paste is connected to a gold wire, and the silicon nitride film, the conductive silver paste and the gold wire are covered with organic potting silica gel.
[0008] Furthermore, the alloy composition of the antenna electrode is composed of 10 nm thick nickel, 80 nm thick germanium-gold alloy and 200 nm thick gold, which is coated on a semi-insulating gallium arsenide substrate by electron beam evaporation (EBE).
[0009] One of the purposes of the present invention is to provide a method for manufacturing the above-mentioned photoconductive antenna, transplanting relatively mature technologies in the microelectronics, semiconductor and other industries such as silicon nitride and organic potting silicone into the field of photogenerated terahertz to achieve improved device performance.
[0010] The technical solution adopted by the present invention to solve the technical problem is: a method for manufacturing a photoconductive antenna, comprising the following steps: In the first step, the semi-insulating gallium arsenide substrate is placed in acetone, isopropanol, and deionized water in turn, and cleaned using ultrasound, and then the surface is blown dry using a nitrogen gun; In the second step, the antenna electrodes and positioning mark patterns are transferred to the semi-insulating gallium arsenide substrate using conventional photolithography or electron beam exposure techniques; In the third step, 10nm thick nickel metal, 80nm thick germanium-gold alloy and 200nm thick gold are sequentially deposited on the semi-insulating gallium arsenide substrate using an electron beam evaporation coating machine, and ultrasonically cleaned using acetone and isopropyl alcohol in turn, and then debonded and dried using a nitrogen gun; The fourth step is to deposit a 300 nm thick silicon nitride film on the semi-insulating gallium arsenide substrate at a substrate temperature of 300°C using plasma enhanced vapor deposition; The fifth step is to transfer the circular opening pattern onto the semi-insulating gallium arsenide substrate using conventional photolithography or electron beam lithography technology; Step 6: Reactive ion beam etching of the silicon nitride film on the semi-insulating gallium arsenide substrate is performed, and ultrasonic cleaning is performed using acetone and isopropyl alcohol in sequence, and then the film is debonded using a nitrogen gun; Step 7: Place the semi-insulating gallium arsenide substrate in a rapid annealing furnace for annealing; set the annealing temperature to 300-400° C. and the annealing time to 60 seconds; In the eighth step, a gold wire with a length of 1 to 2 cm is placed at the circular opening, and then a conductive silver paste is applied to the junction of the gold wire and the semi-insulating gallium arsenide substrate, and the gold wire is connected to the conductive silver paste applied on the circular opening, and the semi-insulating gallium arsenide substrate is placed in a hot air oven and baked at 80° C. for 30 minutes to solidify the conductive silver paste; In the ninth step, after the conductive silver paste is solidified, 50uL of organic potting silicone is dropped onto the semi-insulating gallium arsenide substrate and waited for it to solidify to obtain a photoconductive antenna.
[0011] Furthermore, the first step is to place the semi-insulating gallium arsenide substrate in an HMDS baking machine and set the chamber temperature to 120°C; after the baking is completed, the semi-insulating gallium arsenide substrate is placed on a spin coating table, and the pre-thawed photoresist of model AZ514 is poured on the substrate under yellow light conditions, and immediately spread the glue at a low speed of 1200RPM for 30 seconds, and then the speed is increased to 2000RPM for 5 seconds; after the spin coating is completed, the semi-insulating gallium arsenide substrate is placed on a heating table and baked at 95°C for 5 minutes until the glue is completely cured; the semi-insulating gallium arsenide substrate is placed in a UV exposure machine, and a mask with an electrode pattern is inserted for exposure for 10 seconds; after the exposure is completed, the semi-insulating gallium arsenide substrate is placed in a 3.28% NMD solution and immersed for 90 seconds for development, then rinsed with deionized water, and finally blown dry with a nitrogen gun.
[0012] Furthermore, the third step is to place the semi-insulating gallium arsenide substrate in an electron beam evaporation coating machine, set the substrate temperature to 50°C, first evaporate 10nm of nickel at a rate of 1Å / s, then evaporate 80nm of germanium-gold alloy at a rate of 1Å / s, and finally evaporate 200nm of gold at a rate of 1.5Å / s; after the evaporation is completed, the semi-insulating gallium arsenide substrate is placed in an acetone solution and soaked for 24 hours, and after the metal on the photoresist is stripped, it is immersed in an isopropanol solution, and then blown dry with a nitrogen gun.
[0013] Furthermore, the fourth step is to place the semi-insulating gallium arsenide substrate into PECVD, set the temperature to 300°C, and grow silicon nitride for 1121 seconds under 140sccmSiH, 13sccmNH3, and 200sccmAr to obtain a silicon nitride film with a thickness of 300nm.
[0014] Furthermore, the fifth step is to place the semi-insulating gallium arsenide substrate in an HMDS baking machine and set the chamber temperature to 120°C; after the baking is completed, place the semi-insulating gallium arsenide substrate on a spin coating table, pour the pre-thawed photoresist of model AZ4620 on the substrate under yellow light conditions, and immediately spread the glue at a low speed of 500RPM for 5 seconds, then increase the speed to 1500r / min for 60 seconds, and then increase the speed to 4000r / min for 5 seconds; after the spin coating is completed, place the semi-insulating gallium arsenide substrate on a heating table and bake at 100°C for 10 minutes until the glue is completely cured; place the semi-insulating gallium arsenide substrate in an ultraviolet exposure machine, insert a mask with a circular opening pattern, and expose for 10 seconds; after the exposure is completed, place the semi-insulating gallium arsenide substrate (1) in a 2.38% NMD solution and soak for 4 minutes for development, then rinse with deionized water, and finally blow dry with a nitrogen gun.
[0015] Furthermore, the sixth step is to place the semi-insulating gallium arsenide substrate into a reactive ion beam etcher (RIE), and etch for 340 seconds under 25sccmCHF3, 10scmmCF4 and 10sccmAr; after etching, place the semi-insulating gallium arsenide substrate in an acetone solution for 1 hour, and then place it in an isopropanol solution after the photoresist is dissolved, and then blow dry with a nitrogen gun.
[0016] The beneficial effects of the present invention are: The present invention arranges a silicon nitride film of a certain thickness on a semi-insulating gallium arsenide substrate with an antenna electrode, utilizes the thin film interference effect to enhance the absorption of laser light, and increases the insulation performance of the device; at the same time, an additional layer of convex organic potting silicone is arranged on the silicon nitride film to increase the insulation and thermal conductivity of the device and to produce a focusing effect on the laser light.
[0017] The present invention utilizes the anti-reflection principle of thin film interference to increase the absorption of incident laser light; at the same time, it reduces the dark current of the device, reduces the heating of the device, and thus increases its pressure resistance. The present invention utilizes organic potting silica gel to increase the insulation of the device, and at the same time increases its thermal conductivity, which can quickly conduct away the heat of the chip. At the same time, the silica gel can produce a convergence effect on the laser, making the laser power more concentrated and improving the antenna emission efficiency.
[0018] Compared with traditional photoconductive antennas, the voltage resistance and radiation field strength of the present invention are significantly improved. The terahertz wave amplitude of the manufactured photoconductive antenna is increased by about 6 times, and the terahertz spectrum width is extended from 1.5THz to about 3THz. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a schematic diagram of the three-dimensional structure of the photoconductive antenna of the present invention; Figure 2is a front view of the photoconductive antenna of the present invention; Figure 3 It is a planar structural diagram of the antenna electrode and the circular opening of the present invention; Figure 4 This is a graph showing the change of terahertz electric field intensity over time based on the terahertz time-domain spectrometer test; Figure 5 It is the frequency spectrum obtained based on fast Fourier transform; Figure 6 This is a graph showing how reflectivity changes with the wavelength of the incident laser based on simulation using the finite-difference time-domain method.
[0020] The reference numerals of the figures are: 1—semi-insulating gallium arsenide substrate, 2—antenna electrode, 3—silicon nitride film, 4—circular opening, 5—organic potting silicone, 6—gold wire. DETAILED DESCRIPTION
[0021] The following is a further detailed, clear and complete description of how the present invention is implemented in conjunction with specific embodiments and drawings. Example 1
[0022] Reference Figure 1 , Figure 2 and Figure 3 As shown, the present invention discloses a photoconductive antenna with silicon nitride and organic potting silica gel, comprising a semi-insulating gallium arsenide substrate 1 and an antenna electrode 2 composed of an alloy and distributed symmetrically on the semi-insulating gallium arsenide substrate 1. The semi-insulating gallium arsenide substrate 1 and the antenna electrode 2 are covered with a silicon nitride film 3, and a circular opening for the antenna electrode 2 to be led out is opened on the silicon nitride film 3. The opening is coated with a conductive silver paste, and the conductive silver paste is connected to a gold wire 6. The organic potting silica gel 5 is covered on the silicon nitride film 3, the conductive silver paste and the gold wire 6. The alloy composition of the antenna electrode 2 is composed of 10nm thick nickel, 80nm thick germanium-gold alloy and 200nm thick gold, and is covered on the semi-insulating gallium arsenide substrate 1 by electron beam evaporation (EBE). Example 2
[0023] The invention discloses a method for manufacturing a photoconductive antenna having silicon nitride and organic encapsulating silica gel, and the steps are as follows.
[0024] In the first step, the semi-insulating gallium arsenide substrate 1 is placed in acetone, isopropanol, and deionized water in sequence, and is cleaned by ultrasonic cleaning, and then the surface is dried by a nitrogen gun.
[0025] The specific steps are as follows: placing the semi-insulating gallium arsenide substrate 1 in an HMDS baking machine, and setting the chamber temperature to 120°C; placing the semi-insulating gallium arsenide substrate 1 on a spin coating table after the baking is completed, pouring the pre-thawed photoresist of model AZ514 on the substrate under yellow light conditions, and immediately performing glue spreading at a low speed of 1200RPM for 30 seconds, and then increasing the speed to 2000RPM for 5 seconds; placing the semi-insulating gallium arsenide substrate 1 on a heating table after the spin coating is completed, and baking at 95°C for 5 minutes until the glue is completely cured; placing the semi-insulating gallium arsenide substrate 1 in an ultraviolet exposure machine, inserting a mask with an electrode pattern for exposure for 10 seconds; after the exposure is completed, placing the semi-insulating gallium arsenide substrate 1 in a 3.28% NMD solution for 90 seconds for development, then rinsing with deionized water, and finally drying with a nitrogen gun.
[0026] The semi-insulating gallium arsenide substrate 1 is prepared by a liquid-pull direct sealing method and has a crystal orientation of (100).
[0027] In the second step, the antenna electrode 2 and the positioning mark pattern are transferred to the semi-insulating gallium arsenide substrate 1 by conventional photolithography or electron beam exposure technology.
[0028] In the third step, 10 nm thick nickel metal, 80 nm thick germanium-gold alloy and 200 nm thick gold are sequentially deposited on the semi-insulating gallium arsenide substrate 1 using an electron beam evaporation coating machine, and ultrasonically cleaned using acetone and isopropyl alcohol in turn, and then debonded and dried using a nitrogen gun.
[0029] The specific steps are to place the semi-insulating gallium arsenide substrate 1 in an electron beam evaporation coating machine, set the substrate temperature to 50°C, first evaporate 10nm of Ni at a rate of 1Å / s, then evaporate 80nm of AuGe alloy at a rate of 1Å / s, and finally evaporate 200nm of Au at a rate of 1.5Å / s; after the evaporation is completed, place the semi-insulating gallium arsenide substrate 1 in an acetone solution and soak it for 24 hours, after the metal on the photoresist is stripped off, soak it in an isopropanol solution, and then blow it dry with a nitrogen gun.
[0030] In the fourth step, a 300 nm thick silicon nitride film 3 is deposited on the semi-insulating gallium arsenide substrate 1 at a substrate temperature of 300° C. using plasma enhanced vapor deposition.
[0031] The specific steps are to place the semi-insulating gallium arsenide substrate 1 in PECVD, set the substrate temperature to 300°C, and grow silicon nitride for 1121 seconds under 140sccmSiH, 13sccmNH3, and 200sccmAr to obtain a silicon nitride film 3 with a thickness of 300nm. Figure 6 As shown, the anti-reflection effect of the 300nm silicon nitride film 3 is greatly improved compared with the film without the silicon nitride film 3.
[0032] In the fifth step, the circular opening 4 pattern is transferred to the semi-insulating gallium arsenide substrate 1 by conventional photolithography or electron beam exposure technology.
[0033] The specific steps are as follows: placing the semi-insulating gallium arsenide substrate 1 in a HMDS baking machine, setting the chamber temperature to 120°C; placing the semi-insulating gallium arsenide substrate 1 on a spin coating table after the baking is completed, pouring the pre-thawed photoresist of model AZ4620 on the substrate under yellow light conditions, and immediately performing glue spreading at a low speed of 500RPM for 5s, then increasing the speed to 1500r / min for 60s, and then increasing the speed to 4000r / min for 5s; placing the semi-insulating gallium arsenide substrate 1 on a heating table after the spin coating is completed, and baking at 100°C for 10min until the glue is completely cured; placing the semi-insulating gallium arsenide substrate 1 in a UV exposure machine, inserting a mask with a circular opening 4 pattern for exposure for 10s; after the exposure is completed, placing the semi-insulating gallium arsenide substrate 1 in a 2.38% NMD solution for 4min for development, then rinsing with deionized water, and finally drying with a nitrogen gun.
[0034] In the sixth step, the semi-insulating gallium arsenide substrate 1 is etched using a reactive ion beam, and ultrasonically cleaned using acetone and isopropanol in sequence, and then debonded using a nitrogen gun.
[0035] The specific steps are to place the semi-insulating gallium arsenide substrate 1 into a reactive ion beam etcher (RIE), and etch for 340 seconds under 25sccmCHF3, 10scmmCF4 and 10sccmAr; after the etching is completed, the semi-insulating gallium arsenide substrate 1 is placed in an acetone solution and immersed for 1 hour, and then immersed in an isopropanol solution after the photoresist is dissolved, and then blown dry with a nitrogen gun.
[0036] The seventh step is to place the semi-insulating gallium arsenide substrate 1 in a rapid annealing furnace for annealing; the annealing temperature is set to 300-400° C. and the annealing time is set to 60 seconds.
[0037] In the eighth step, a gold wire 6 with a length of 1 to 2 cm is placed at the circular opening 4, and then a conductive silver paste is applied to the junction of the gold wire 6 and the semi-insulating gallium arsenide substrate 1, and the gold wire 6 is connected to the conductive silver paste applied on the circular opening; the semi-insulating gallium arsenide substrate 1 is placed in a hot air oven and baked at 80°C for 30 minutes to solidify the conductive silver paste.
[0038] In the ninth step, after the conductive silver paste is cured, 50uL of organic potting silica gel 5 is dropped onto the semi-insulating gallium arsenide substrate 1. The breakdown electric field strength of the organic potting silica gel 5 is greater than 20kV / mm, and it presents a convex shape after curing, thereby obtaining a photoconductive antenna.
[0039] The specific steps are to stir the two components AB of the organic potting silicone 5 evenly and mix them together in a mass ratio of 1:1, then use a pipette to absorb 50uL of the organic potting silicone and drop it on the semi-insulating gallium arsenide substrate 1; then place the semi-insulating gallium arsenide substrate 1 in a hot air oven and bake it at 80°C for 30 minutes to solidify the organic potting silicone 5.
[0040] The characteristics of the product prepared by the present invention are as follows: Figure 4 and Figure 5 shown. Figure 4 The figure shows the change of terahertz electric field intensity over time based on the terahertz time domain spectrometer test: the dotted line is the terahertz radiation intensity of the traditional photoconductive antenna (PCA) not covered with silicon nitride film 3 and organic encapsulating silica gel 5; the solid line is the terahertz radiation intensity of the photoconductive antenna with silicon nitride film 3 and organic encapsulating silica gel 5 of the present invention. Figure 5 The frequency spectrum obtained based on fast Fourier transform is shown: the dotted line is the spectrum of the traditional photoconductive antenna (PCA) not covered with silicon nitride film 3 and organic encapsulating silica gel 5; the solid line is the spectrum of the photoconductive antenna with silicon nitride film 3 and organic encapsulating silica gel 5 of the present invention.
[0041] The terahertz wave amplitude of the product manufactured by the method of the present invention is increased by about 6 times, and the terahertz spectrum width is extended from 1.5THz to about 3THz. The reflectivity simulated by the finite difference time domain method changes with the wavelength of the incident laser. Figure 6 As shown: the dotted line is the reflectivity of the conventional photoconductive antenna (PCA); the solid line is the reflectivity of the photoconductive antenna of the present invention having a 300 nm thick silicon nitride film 3 .
[0042] The present invention is obtained after performance characterization by the following equipment.
[0043] The light source used in the experiment is a mode-locked femtosecond laser developed by Daheng New Era Company, with a central wavelength of 800nm, a pulse width of less than 50fs, a repetition frequency of 80MHz, and a maximum output power of 400mW. The laser is first split into pump light and probe light. The pump light is converged onto the PCA chip through variable optical attenuation and focusing lenses. The terahertz pulses radiated by the PCA chip are focused onto the ZnTe crystal through two off-axis parabolic mirrors. The probe light is also converged onto the ZnTe crystal through an optical delay stage. The ZnTe crystal changes the polarization state of the pulsed laser under the modulation of the terahertz wave, and is detected by a balanced detector through a Wollaston prism. The phase-locked amplifier amplifies and records the voltage signal output by the balanced detector, and outputs a sinusoidal voltage signal of the same frequency, which is amplified and applied to both ends of the PCA electrode. The phase-locked frequency is set to 8.337kHz, the integration time is 30ms, and the tests are all carried out in an atmospheric environment.
[0044] The above embodiments are only illustrative of the principles and effects of the present invention, as well as some embodiments of its application. For those skilled in the art, several modifications and improvements may be made without departing from the creative concept of the present invention, and all of these belong to the protection scope of the present invention.
Claims
1. A photoconductive antenna, characterized in that: The invention comprises a semi-insulating gallium arsenide substrate (1) and an antenna electrode (2) centrally symmetrically distributed on the semi-insulating gallium arsenide substrate (1); the semi-insulating gallium arsenide substrate (1) and the antenna electrode (2) are covered with a silicon nitride film (3); a circular opening (4) for leading the antenna electrode (2) is formed on the silicon nitride film (3); a conductive silver paste is provided in the circular opening (4); the conductive silver paste is connected to a gold wire (6); and the silicon nitride film (3), the conductive silver paste and the gold wire (6) are covered with an organic potting silica gel (5).
2. A photoconductive antenna according to claim 1, characterized in that: The antenna electrode (2) is made of nickel, germanium-gold alloy and gold, and is covered on a semi-insulating gallium arsenide substrate (1) by electron beam evaporation.
3. A method for manufacturing a photoconductive antenna as claimed in claim 1, characterized in that: The steps include: In the first step, the semi-insulating gallium arsenide substrate (1) is ultrasonically cleaned in acetone, isopropanol, and deionized water in sequence, and then blown dry with a nitrogen gun; The second step is to transfer the antenna electrode (2) and the positioning mark pattern onto the semi-insulating gallium arsenide substrate (1); The third step is to use an electron beam evaporation coating machine to sequentially deposit nickel metal, germanium-gold alloy and gold on the semi-insulating gallium arsenide substrate (1), and then use acetone and isopropyl alcohol to ultrasonically clean it, and then use a nitrogen gun to remove the glue and dry it; The fourth step is to deposit a silicon nitride film (3) on the semi-insulating gallium arsenide substrate (1) by plasma enhanced vapor deposition; Step 5, transferring the circular opening (4) pattern onto the semi-insulating gallium arsenide substrate (1); Step 6: using reactive ion beam to etch the silicon nitride film (3) on the semi-insulating gallium arsenide substrate (1), and then using acetone and isopropanol to ultrasonically clean it, and then using a nitrogen gun to remove the glue; Step 7: placing the semi-insulating gallium arsenide substrate (1) into an annealing furnace and annealing at 300-400° C. for 60 seconds; Step 8: placing the gold wire (6) at the circular opening (4), then applying conductive silver paste to the junction between the gold wire (6) and the semi-insulating gallium arsenide substrate (1), connecting the gold wire (6) and the conductive silver paste, and baking to solidify the conductive silver paste; In the ninth step, after the conductive silver paste is cured, the organic potting silica gel (5) is dripped onto the semi-insulating gallium arsenide substrate (1) and cured to obtain a photoconductive antenna.
4. The method for manufacturing a photoconductive antenna according to claim 3, characterized in that: The first step is to place the semi-insulating gallium arsenide substrate (1) in an HMDS baking machine and set the chamber temperature to 120°C; after the baking is completed, the semi-insulating gallium arsenide substrate (1) is placed on a spin coating table, and a photoresist is poured on the substrate under yellow light conditions, and the photoresist is spread at 1200RPM for 30 seconds, and then the speed is increased to 2000RPM for 5 seconds; after the spin coating is completed, the semi-insulating gallium arsenide substrate (1) is placed on a heating table and baked at 95°C for 5 minutes until the photoresist is completely cured; the semi-insulating gallium arsenide substrate (1) is placed in an ultraviolet exposure machine, and a mask with an electrode pattern is inserted for exposure for 10 seconds; then the semi-insulating gallium arsenide substrate (1) is placed in an NMD solution and immersed for 90 seconds for development, and then rinsed with deionized water, and finally blown dry with a nitrogen gun.
5. The method for manufacturing a photoconductive antenna according to claim 4, characterized in that: The third step is to place the semi-insulating gallium arsenide substrate (1) in an electron beam evaporation coating machine, set the substrate temperature to 50°C, first evaporate 10nm of nickel at a rate of 1Å / s, then evaporate 80nm of germanium-gold alloy at a rate of 1Å / s, and finally evaporate 200nm of gold at a rate of 1.5Å / s; after the evaporation is completed, place the semi-insulating gallium arsenide substrate (1) in an acetone solution and soak it for 24 hours, wait for the metal on the photoresist to be stripped, soak it in an isopropanol solution, and then blow dry it with a nitrogen gun.
6. The method for manufacturing a photoconductive antenna according to claim 5, characterized in that: The fourth step is to place the semi-insulating gallium arsenide substrate (1) into PECVD, set the temperature to 300°C, and grow silicon nitride for 1121 seconds under 140sccmSiH, 13sccmNH3, and 200sccmAr to obtain a silicon nitride film (3) with a thickness of 300nm.
7. The method for manufacturing a photoconductive antenna according to claim 6, characterized in that: The fifth step is to place the semi-insulating gallium arsenide substrate (1) in an HMDS baking machine and set the chamber temperature to 120°C; after the baking is completed, the semi-insulating gallium arsenide substrate (1) is placed on a spin coating table, a photoresist is poured on the substrate under yellow light conditions, and the photoresist is immediately spread at a speed of 500RPM for 5 seconds, then the speed is increased to 1500r / min for 60 seconds, and then the speed is increased to 4000r / min for 5 seconds; after the spin coating is completed, the semi-insulating gallium arsenide substrate (1) is placed on a heating table and baked at 100°C for 10 minutes until the photoresist is completely cured; The semi-insulating gallium arsenide substrate (1) is placed in a UV exposure machine, and a mask having a circular opening (4) pattern is inserted therein for exposure for 10 seconds; After the exposure is completed, the semi-insulating gallium arsenide substrate (1) is immersed in the NMD solution for 4 minutes for development, then rinsed with deionized water, and finally dried with a nitrogen gun.
8. The method for manufacturing a photoconductive antenna according to claim 7, characterized in that: The sixth step is to place the semi-insulating gallium arsenide substrate (1) in a reactive ion beam etcher, and etch for 340 seconds under 25 sccm CHF3, 10 scmm CF4 and 10 sccm Ar; after etching, place the semi-insulating gallium arsenide substrate (1) in an acetone solution for 1 hour, wait for the photoresist to dissolve, place it in an isopropanol solution, and then blow dry it with a nitrogen gun.